Development of Inventory Model to Reduce Total Inventory Costs at RSUD Mentawai - Inaya Izzati; Dida Diah Damayanti (School of Industrial and System Engineering, Telkom University, 2023)
The inventory policy problem is a problem in the inventory system related to how to ensure that each usage demand can be met at minimal cost. In the healthcare industry, it is imperative that the procurement and use of stock is not only cost-effective, but also that the required stock is always available. Discrepancies between total inventory and usage can lead to damage to BMHP inventory as the items have expiry dates, as well as excess total inventory costs. The problem of total inventory costs exceeding the budget occurs because overstock is 83% of the total need, overstock is caused by an excessive number of drug orders purchased. The purpose of this study is to reduce the total cost of inventory by considering expiry costs, inspection cost, shortage cost, order cost, holding cost using the EOQ method. The first stage in this study is to calculate the optimal order quantity value, then find the expected number of drug expirations. These results will be used to calculate the total inventory cost of five types of medical materials. for the inspection cost value, if the number of expired medical materials is above 20, the inspection cost value is not equal to zero. The calculation results found that the total inventory cost was Rp. 162,904,965, this cost is less than the actual cost of Rp. 185,843,346.00 with a difference of 12%.